2021
DOI: 10.1002/qre.2966
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced double homogeneously weighted moving average control chart to monitor process location with application in automobile field

Abstract: The memory control charts, including cumulative sum (CUSUM) and exponentially weighted moving average (EWMA) control charts, are widely used to monitor small-to-moderate shifts in the process location and/or dispersion. The homogenously weighted moving average (HWMA) control chart is the advanced form of the EWMA control chart to monitor process location shifts. Besides, the auxiliary information-based memory control charts efficiently monitor process location shifts. The objective of this study is to propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…Research that considers measurement errors in adaptive synthetic charts is also suggested, as well as higher‐order autoregressive models AR(p$p$), p>1$p>1$, and multivariate statistical process control such as the chart developed by Xue and Qiu 41 and Bersimis et al 42 . In addition, this methodology can be extended to combinations of charts, such as the one developed by Haq and Munir, 43 and memory control charts, that are widely used to detect small and moderate changes 44 …”
Section: Discussionmentioning
confidence: 99%
“…Research that considers measurement errors in adaptive synthetic charts is also suggested, as well as higher‐order autoregressive models AR(p$p$), p>1$p>1$, and multivariate statistical process control such as the chart developed by Xue and Qiu 41 and Bersimis et al 42 . In addition, this methodology can be extended to combinations of charts, such as the one developed by Haq and Munir, 43 and memory control charts, that are widely used to detect small and moderate changes 44 …”
Section: Discussionmentioning
confidence: 99%
“…The data comprise 30 samples, each size n = 5 given in Table 7. In order to implement the proposed HEWMA1 and HEWMA2 control along with CH and CEWMA charts, following [23,48], an upward shift of size ÎŽ = 1.25 is introduced artificially after sample number 16 [49,50]. At ARL 0 = 200, the smoothing parameter values λ 1 = 0.1, λ 2 = 0.05 are used, which provides the width of the the HEWMA1, and HEWMA2, CH and CEWMA charts, respectively, given as L + HEWMA1 = 1.365, L + HEWMA2 = 1.399, L + CH = 1.303 and L + CEWMA = 2.198.…”
Section: Important Points Of the Studymentioning
confidence: 99%
“…p as the time series, where p was the length of the time series. Hence, the MA of period q at time l was calculated using Equation ( 8) [35][36][37][38][39]:…”
Section: Moving Averagementioning
confidence: 99%